Influence of GGBS- based Geopolymer Aggregate on Compressive Strength of Concrete - et. al., Mrs. Jayadurgalakshmi.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Concrete is the most widely used building component in the world due to its versatility, low cost and durability. Most common coarse aggregate used in the construction are stones which is obtained from quarry. The demand for coarse aggregate in the construction industry has consequently increased due to the extensive use of natural resources. It has necessitated research into alternative materials of construction. This research aims to find the alternate material for coarse aggregate by using Ground Granulated Blast furnace Slag (GGBS) clinker and to determine the hardened properties of non-conventional concrete in M20 Grade. The aggregate utilized in this work is an Eco friendly material, which replace the conventional coarse aggregate to preserve the depletion of natural resources. It is abundantly available than the conventional aggregate and reduce pollution. This paper focuses on investigating characteristics of concrete with replacement of coarse aggregate by GGBS Clinker. This study deals with the GGBS clinker advantages and limitations in concrete. The usage of GGBS clinker serves as a replacement of conventional aggregate to reduce the depletion of conventional building materials. It serves as an Eco friendly way of utilizing the by- product without dumping it on ground.